Comparative clinical study of pulsatile and non-pulsatile perfusion in 350 consecutive patients. Issue 5 (May 1982) - Taylor, K M; Bain, W H; Davidson, K G; Turner, M A
Abstract : Pulsatile perfusion has been shown to offer significant haemodynamic advantages over non-pulsatile perfusion in many experimental studies. Clinical acceptance of pulsatile perfusion during cardiac surgical procedures has, however, been hampered by the lack of technologically satisfactory pulsatile pump systems, and by inadequate clinical experience of routine use of pulsatile perfusion. The recent introduction of reliable pulsatile pump systems with low haemolysis characteristics has made possible the clinical validation of the previous experimental studies. We describe the results of a prospective study of mortality, haemodynamic morbidity, and haematological status, in 350 consecutive adult patients submitted to cardiopulmonary bypass procedures in a surgical unit over a 12-month period. One hundred and seventy five patients were perfused with conventional non-pulsatile flow and 175 with pulsatile flow, using a modified roller-pump pulsatile system (Cobe-Stockert). The groups were closely similar in terms of preoperative characteristics, referral category, and pathology requiring surgery. Operative techniques, bypass parameters, and anaesthetic regime were standardised in both groups. The results were as follows. (1) Total mortality was significantly lower in the pulsatile group (4.6%) compared with the non-pulsatile group (10.3%), p = 0.06. (2) The incidence of deaths attributable to post-perfusion low cardiac output was significantly lower in the pulsatile group (1.1% compared with 6.3%, p = 0.02). (3) Requirement for mechanical (intra-aortic balloon) or drug circulatory support was significantly lower in the pulsatile group. (4) The use of pulsatile perfusion was not associated with any increase in haemolysis, blood cell depletion, or postoperative bleeding problems.